Der Seth-Name Ramses’ II.: Ein Beleg aus dem Baal-Tempel in Bahr el-Baqar - Iskander, John Moussa; Abd el-Karim, Ehab Gamil (Mitteilungen des Deutschen Archäologischen Instituts Kairo, 2024)
The article describes a stela from the 11ᵗʰ year of Ramesses II found in the area of Bahr el-Baqar with a scene of the king presenting a captive to a god depicted in Asiatic iconography. The text below lists the royal names of the king in which the falcon sign of Horus has been replaced by the Seth animal. However, the significance of the stela is owed to the fact that it is the only Egyptian source till now that mentions a temple of the God Baal at the eastern borders of the Delta.